Managing Stress for Special School Teachers in Assisting Children with Special Needs - Kurnia, Arini; Rosangela, Martucci; Z, Sri Putri Rahayu; Ahmad, Mutia Aini (Darussalam: Journal of Psychology and Educational, 2024)
Many teachers of special schools (SLB) experience stress whether they realize it or not. Teachers who are under pressure can experience discomfort which can lead to depression, lack of motivation and frustration. The stress experienced by teachers of special schools has a negative impact on teachers of special schools and children with special needs (ABK), both physically, mentally, emotionally and behaviorally. Therefore, this problem must be addressed so that it does not have a negative impact on special needs school teachers and children with special needs. The purpose of this study is to determine the process of stress management strategies in overcoming these problems. This descriptive qualitative research was conducted using data collection techniques in the form of literature review. This study shows that coping with stress is an effort that consists of changes in cognitive and attitude in managing and overcoming pressure from within the individual and from outside the individual. The stress management strategy for Special School teachers consists of problem-oriented and emotional coping. Overcoming focus is a stress management strategy can be influenced by some cultural background, experience in solving problems, environmental factors, personality, self-image and social factors. It is believed that this research will greatly assist Special School teachers to improve the quality of education and training for Children with Special Needs, and through stress management can make people aware of the problems they face and make them more careful in their actions and take ways to solve problems.